Produtividade de óleo-resina de Copaifera sp. : relações dendrométricas, edáficas e etática - Roquette, José Guilherme (2014)
The objective of this study was to examine dendrometric, edaphic and of age relationships with productivity of oleoresin Copaifera sp. in Semideciduous Seasonal Forest in the central north region of the State of Mato Grosso, Brazil. We sampled 30 Copaifera sp. for extraction of oleoresin for a period of 24 hours, using auger with 3/4". In addition to the oleoresin, information was collected regarding the size of the trees and of the edaphics characteristics of topsoil in around each individual. Also, were removed wood cylinders of 15 of the 30 trees sampled to determination of age and mean annual increment (MAI) of DBH, whereas estimates of these variables were carried out by through regression analysis to those who have not had the cylinders collected. Upon completion of the data for all variables, there was the descriptive statistics for the productivity of oleoresin, in addition to reporting the proportions observed between productive and non-productive trees in the studied area. Was applied the principal component analysis to verify which of the variables collected are related to the productivity of oleoresin , and later, posteriorly, to adjust a equation using regression analysis for predicting this productivity. The model that better adjusted to estimate the age according to the DBH presented value of adjusted coefficient determination = 0,616 and standard error estimate = 4.42. The average productivity of the population studied was 0.124 L, with coefficient of variation = 349.9% and 30% of productive trees. The proportion of productive trees increased with DBH class, being reduced to reach the bigger class. Regarding age, the proportion of productive individuals also increased with the classes, but not being perceived decline to reach the bigger class, while with respect to the IMA of DBH the opposite happened. After the principal component analysis, the only variable correlated with productivity oleoresin was the height of the bole, in which the better model adjusted presented adjusted coefficient determination = 0,846 and standard error estimate = 13.11. Thus, it was found that the productivity of oleoresin copaiba has a positive and significant correlation with the height of the shaft, while with the other dendrometric variables as well as variables topsoil and age, no significant correlation.